Mobile App Design Process to Promote Physical Activity in Cancer Care: Findings about Physical Activity and Quality of Life - azemmour, Youness; Beddaa, Hassan; Chamlal, Hamid; Elkhalloufi, Fahd; Rouani, Abdeljabbar; Fares, Rachid; Boutayeb, Saber (International Journal of Innovative Research in Medical Science, 2024)
Background: Physical activity is recognized as a supportive care in cancer management. Mobile apps have become a common and effective method of promoting physical activity in cancer. The results presented in this paper come from the mobile app design process at the National Institute of Oncology in Morocco. Objectives: This study aimed to describe the short-term changes in physical activity and quality of life in post-cancer treatment, after participating in this mobile app design process. Methods: Twenty-four post-treatment cancer patients participated in a user-centered design process to create a mobile physical activity application. The data collected was based on self-monitoring and self-assessment. The assessment was requested at the beginning and the end of the participation using the International Physical Activity Questionnaire and the SF-12 questionnaire. Results: The physical activity volume rose from 323 MET-min/week (160–410) in the first evaluation to 540 MET-min/week (460–730) after the mobile app participation. Eight of 11 participants have been moved from a low physical activity level to a moderate level. The physical health score rose from 57 (63-37) to 65 (72-54). The mental health score rose from 57 (63-37) to 65 (72-54). Conclusions: A short-term improvement in physical activity and quality of life was observed in post-treatment cancer patients. However, stronger studies are needed to confirm these results.